Utilization Of Kepok Banana Skin As a As a Mixture of Plastic for Biobags - Ramadan, Awal; Pulungan, Maimunah Hindun; Suhartini, Sri (University of Brawijaya, 2019)
The research aims to get concentration of addition of Kepok banana flour and glycerol to produce good mechanical quality in the manufacture of plastic biobags. The study was designed using a randomized design group with 2 factors. The first factor used is the proportion of raw material for banana peel flour: banana starch (P) which consists of 3 levels. The second factor is the concentration of glycerol (G) which consists of 2 levels. Parameters observed for plastic biobags include: tensile strength, percentage elongation, elasticity, swelling, brightness, thickness, moisture content, and biodegradation. Analysis data obtained, processed using analysis of variance (ANOVA), If the results of the analysis of variance are significant differences between factors, it will be followed by a BNT test of 5%. Based on the results of physical and mechanical properties analysis, the best plastic biobags were found in the treatment proportion of 25% skin flour: 75% banana starch with a concentration of 2%. with a yield rate of 11,78%, tensile strength value of 0,41 N/cm2Â , percentage elongation 10%, elasticity of 0,035 Mpa, swelling of 57,17%, brightness level of 29,97 thickness 0,956 mm, moisture content 11,77% and degraded completely for 22 days with percentage biodegradation 55,23%.